Real-world therapeutic performance of pirfenidone for connective tissue disease-associated interstitial lung diseases - Yuan, Xueting; Yu, Chen; Liu, Shengyun; Shu, Qiang; Duan, Xinwang; Tang, Lin; Peng, Liying; Zhou, Shuang; Wu, Chanyuan; Zhao, Jiuliang; Xu, Dong; Song, Lan; et al. (Therapeutic advances in respiratory disease, 2024)
Background: Pirfenidone (PFD) is commonly applied for antifibrotic treatment in patients with idiopathic pulmonary fibrosis but has rarely been studied in cases with connective tissue disease-associated interstitial lung diseases (CTD-ILDs). Objectives: We aimed to examine the efficacy of PFD in patients with CTD-ILD based on real-world data. Design: A retrospective cohort study. Methods: This study assessed the clinical features of CTD-ILD patients with or without a 6-month PFD treatment. A linear mixed effects model was employed to evaluate the effectiveness of PFD in alleviating lung function changes. Differences in response to PFD were analyzed based on CTD subtype, imaging classification, and pattern of pulmonary function at baseline. Results: A total of 289 patients with CTD-ILD were included, with 155 (53.6%) receiving PFD treatment and the remaining constituting the control group. Patients with the usual interstitial pneumonia (UIP) pattern were more likely to receive PFD treatment, and a relatively lower proportion of cases in the PFD group received immunosuppressive therapies compared to the control group (p < 0.05). At the 6-month follow-up, patients in the PFD group demonstrated a more significant improvement in forced vital capacity (FVC) and diffusion capacity for carbon monoxide (DLCO) (ΔFVC%: 2.9% vs 0.45%, p = 0.009; ΔDLCO%: 1.9% vs −1.1%, p = 0.004). In the linear mixed model analysis, there was a statistically significant group-time interaction between FVC% and DLCO% changes over time (FVC%: β = 4.52, p < 0.001; DLCO%: β = 4.13, p = 0.003). Furthermore, subgroup analysis indicated that pirfenidone may have superior therapeutic effects in patients with systemic sclerosis (SSc)-associated ILD, non-UIP pattern, and restrictive pattern of lung function at baseline. Conclusion: This study provided real-world data demonstrating the effectiveness of PFD in terms of lung function improvement in patients with CTD-ILD.